Challenges to wellbeing of faculty and leaders in higher education in the Gulf Cooperation Council - El-Haddad, Rita (2024)
The area of wellbeing in higher education in the Global South is attracting increased attention. While the main focus of past research studies has been on the wellbeing of university students in the Gulf Cooperation Council (GCC), the wellbeing of faculty and leaders in higher education in the region has yet to be explored. The unique cultural contexts within the GCC demand that assumptions of wellbeing from the Global North be challenged. This chapter will review existing research on the wellbeing of faculty and leaders in higher education in the GCC to identify gaps in the literature. Finally, this review will contribute to our understanding of this topic in the GCC and provide suggestions for future research to improve wellbeing in higher education.